Identification of a special cell type as a determinant of the kidney tropism of SARS‐CoV‐2. (29th July 2021) - Lin, Hongchun; Ma, Xinxin; Xiao, Fang; Su, Hua; Shi, Yaling; Liu, Yuntao; Song, Lan; Zhang, Zhongde; Zhang, Chun; Peng, Hui
Abstract : The kidney tropism of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has been well‐validated clinically and often leads to various forms of renal damage in coronavirus disease‐2019 (COVID‐19) patients. However, the underlying mechanisms and diagnostic approaches remain to be determined. We interrogated the expression of virus‐related host factors in single‐cell RNA sequencing (scRNA‐seq) datasets of normal human kidneys and kidneys with pre‐existing diseases and validated the results with urinary proteomics of COVID‐19 patients and healthy individuals. We also assessed the effects of genetic variants on kidney susceptibility using expression quantitative trait loci (eQTLs) databases. We identified a subtype of tubular cells, which we named PT‐3 cells, as being vulnerable to SARS‐CoV‐2 infections in the kidneys. PT‐3 cells were enriched in viral entry factors and replication and assembly machinery but lacked antiviral restriction factors. Immunohistochemistry confirmed positive staining of PT‐3 cell marker SCL36A2 on kidney sections from COVID‐19 patients. Urinary proteomic analyses of COVID‐19 patients revealed that markers of PT‐3 cells were significantly increased, along with elevated viral receptor angiotensin‐converting enzyme 2. We further found that the proportion of PT‐3 cells increased in diabetic nephropathy but decreased in kidney allografts and lupus nephropathy, suggesting that kidney susceptibility varied among these diseases. We finally identified several eQTLs that regulate the expression of host factors in kidney cells. PT‐3 cells may represent a key determinant for the kidney tropism of SARS‐CoV‐2, and detection of PT‐3 cells may be used to assess the risk of renal infection during COVID‐19. Abstract : Through single‐cell analysis, we identified PT‐3 cells, a proximal tubule epithelial cell subtype in human kidney, that are highly susceptible to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. We validated these results using immunostaining and urinary proteomics in coronavirus disease‐2019 (COVID‐19) patients. Our findings provide not only new insights into the mechanism involving SARS‐CoV‐2 infection of the kidney cells, but also a potential strategy for risk assessment of kidney infection among COVID‐19 patients.